EFFECTS OF HERBAL TEAS ON POLYCYSTIC OVARY SYNDROME (PCOS): A LITERATURE REVIEW - Zukri, Nurul Fatehah; Nordin, Noraziah; Azzeri, Amirah (Biomedika, 2025)
Polycystic ovary syndrome (PCOS) is an endocrine disorder that affects women of reproductive age. It is characterized by hormonal imbalances, metabolic disturbances, and anthropometric abnormalities. In recent years, the use of herbal teas as supplemental treatments for PCOS symptoms has gained popularity among people with the condition. This literature review aims to determine the impacts of herbal tea consumption on anthropometric parameters, identifying its effects on metabolic indices, and describing its influences on hormonal profiles. A thorough search of electronic databases was conducted to identify studies investigating the effects of herbal teas such as spearmint, cinnamon, chamomile, red clover, and hibiscus. The review included both observational research and clinical trials. The findings suggest that spearmint demonstrates the strongest evidence particularly for hormonal modulation in women with polycystic ovary syndrome. However, the available evidence is still inconsistent, with variations in study design, tea dosage, duration, and outcome measures. In conclusion, even though some herbal teas show potential as adjuvant therapy for PCOS, additional standardized research is required to prove the effectiveness of herbal teas and establish clear clinical recommendations.